Southeast Asian nations’ regional competitiveness: an exploration through grey relational analysis - Fang, Tzu-Yi; Lin, Sheng-Wei; Lo, Huai-Wei; Wu, Chia-Hao (Technological and Economic Development of Economy, 2022)
This study aims to explore the comparison of the regional competitiveness of the nations targeted by Taiwan’s New Southbound Policy and the key indicators that influence regional competitiveness. Through comparative analysis between each other, we will further select countries and regions that are most suitable for investment and exchange. Regional competitiveness describes the ability of various economies to compete for resources or markets in a region. Exploring regional competitiveness allows the best nations for investment to be identified so that unnecessary costs and losses may be avoided. This paper proposes a multiple attribute decision making method, grey relational analysis (GRA), for solving this kind of problem. This study investigates the regional competitiveness of various nations using competitiveness rankings obtained through the ranking of grey relational ordinals. The study seeks to identify critical factors underlying regional competitiveness. The study variables are grouped into four major factors: economy, human resources, technology, and trade capability. The results reveal that India, Singapore, and Australia are nations with regional competitive advantages. Labor force and technology are indispensable factors for enhancing regional competitiveness. ASEAN countries have greater regional competitiveness than South Asia or Australia and New Zealand. First published online 09 June 2022